Application of Microclimate Modelling and Onsite Survey in Planning Practice Related to an Urban Micro-Environment. (2nd September 2013) - Égerházi, Lilla Andrea; Kovács, Attila; Unger, János
Abstract : Numerical simulations of human thermal comfort conditions were carried out by means of the urban microclimate model ENVI-met in a popular children's playground located in Szeged, Hungary. Bioclimatic conditions were quantified by the Physiologically Equivalent Temperature (PET). Based on the PET values, thermal stress maps were created in two different periods of typical summer and autumn days. The study aims to reveal the seasonal and diurnal spatial patterns of the simulated thermal conditions and thus the degree of heat stress in different parts of the playground. Furthermore, we analysed the momentary spatial distributions of the visitors triggered by the microclimatic conditions of the area. According to the simulation, remarkable differences in the thermal conditions were found depending on the sun elevation and the resulting shaded conditions as well as the radiation of the heated surfaces. The spatial distribution of the visitors seems to be highly influenced by the patterns of the thermal conditions but the location and the preference of the children's playground equipment also affects it. In order to reveal the possible causes of the people's behaviour, an onsite questionnaire survey was conducted on their opinions and possible modification requirements related to the design of the playground.